Recent advances in the adsorption of different pollutants from wastewater using carbon-based and metal-oxide nanoparticles - Rezania, Shahabaldin; Darajeh, Negisa; Rupani, Parveen Fatemeh; Mojiri, Amin; Kamyab, Hesam; Taghavijeloudar, Mohsen (MDPI, 2024)
In recent years, nanomaterials have gained special attention for removing contaminants from wastewater. Nanoparticles (NPs), such as carbon-based materials and metal oxides, exhibit exceptional adsorption capacity and antimicrobial properties for wastewater treatment. Their unique properties, including reactivity, high surface area, and tunable surface functionalities, make them highly effective adsorbents. They can remove contaminants such as organics, inorganics, pharmaceuticals, medicine, and dyes by adsorption mechanisms. In this review, the effectiveness of different types of carbon-based NPs, including carbon nanotubes (CNTs), graphene-based nanoparticles (GNPs), carbon quantum dots (CQDs), carbon nanofibers (CNFs), and carbon nanospheres (CNSs), and metal oxides, including copper oxide (CuO), zinc oxide (ZnO), iron oxide (Fe2O3), titanium oxide (TiO2), and silver oxide (Ag2O), in the removal of different contaminants from wastewater has been comprehensively evaluated. In addition, their synthesis methods, such as physical, chemical, and biological, have been described. Based on the findings, CNPs can remove 75 to 90% of pollutants within two hours, while MONPs can remove 60% to 99% of dye in 150 min, except iron oxide NPs. For future studies, the integration of NPs into existing treatment systems and the development of novel nanomaterials are recommended. Hence, the potential of NPs is promising, but challenges related to their environmental impact and their toxicity must be considered.
Keywords: carbon-based nanoparticles; metal-oxide-based nanoparticles; adsorption; pollutants; wastewater treatment; 32 Biomedical and Clinical Sciences; 40 Engineering; 4004 Chemical Engineering; 3206 Medical Biotechnology; 4018 Nanotechnology; Bioengineering; Nanotechnology